Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4810
|View full text |Cite
|
Sign up to set email alerts
|

Generalized analysis of the deposition/splashing limit for one- and two-component droplet impacts upon thin films

Abstract: Single drop impacts on thin liquid layers are of particular interest because of the ejection of secondary droplets, the so-called splashing. Only a few studies handle the deposition/splashing limit for two-component interaction, where the liquid properties of the impacting drop and wall film differ significantly. This study aims at identifying a unified approach for one-and two-component interactions to determine the deposition/splashing limit. Therefore, a large database of both interactions is considered, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…the review article of Liang & Mudawar (2016)), studies on binary droplet/wall-film systems are rarely found in the literature. Originally studied in the pioneering work of Worthington & Cole (1897) with water and milk, most of the studies on binary systems are with miscible liquid pairs (Thoroddsen, Etoh & Takehara 2006;Geppert et al 2016;Bernard et al 2017;Geppert et al 2017;Kittel, Roisman & Tropea 2018b;Geppert 2019) and focus on splashing limit, crown dynamics or on the viscosities. In contrast, binary systems with exclusively immiscible droplet/wall-film systems have been investigated mainly with respect to the characteristics of the secondary droplets (Shaikh et al 2018) and to the repartition of the droplet and wall-film liquids in the crown depending on the viscosity ratio (Kittel, Roisman & Tropea 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…the review article of Liang & Mudawar (2016)), studies on binary droplet/wall-film systems are rarely found in the literature. Originally studied in the pioneering work of Worthington & Cole (1897) with water and milk, most of the studies on binary systems are with miscible liquid pairs (Thoroddsen, Etoh & Takehara 2006;Geppert et al 2016;Bernard et al 2017;Geppert et al 2017;Kittel, Roisman & Tropea 2018b;Geppert 2019) and focus on splashing limit, crown dynamics or on the viscosities. In contrast, binary systems with exclusively immiscible droplet/wall-film systems have been investigated mainly with respect to the characteristics of the secondary droplets (Shaikh et al 2018) and to the repartition of the droplet and wall-film liquids in the crown depending on the viscosity ratio (Kittel, Roisman & Tropea 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experimental investigations, researchers developed theoretical models to predict the crown evolution, looking for an accurate length scale of crown expansion and its dependence on the impact parameters (i.e., We, Fr, and/or δ * ). Bernard et al [28] concentrated on the crown radius and found an accurate length scale for the crown rim expansion. Yarin and Weiss [29] investigated crown morphology for different operating parameters, and obtained an empirical correlation of the crown radius…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we have discussed another splashing criteria based on Ohnesorge number (Oh) and Reynolds number (Re) in Introduction section, which was presented by Ma et al [23] by summarizing a larger number of researchers' experimental data at various test conditions shown in Figure 11 (right). The black dash line stands for the splashing correlation of OhRe = 17 from Ma et al [23], the rest of four dash lines exhibit the correlations of OhRe 1.25 = 124.3, OhRe 1.25 = 126.7, OhRe 1.17 = 63, and OhRe 1.29 = 197.9 from Geppert et al [49], Cossali et al [50],Vander Wal et al [51], and Bernard et al [52], respectively. Most of blue points from our experiment are below these critical lines while most of red data points are above it.…”
Section: Splashing Criteria As Per the Experimental Investigationmentioning
confidence: 96%